2017
DOI: 10.1021/acs.molpharmaceut.7b00294
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Mechanisms of Intestinal Drug Absorption from Aprepitant Nanoformulations

Abstract: Over recent decades there has been an increase in the proportion of BCS class II and IV drug candidates in industrial drug development. To overcome the biopharmaceutical challenges associated with the less favorable properties of solubility and/or intestinal permeation of these substances, the development of formulations containing nanosuspensions of the drugs has been suggested. The intestinal absorption of aprepitant from two nanosuspensions (20 μM and 200 μM total concentrations) in phosphate buffer, one na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 39 publications
1
26
1
Order By: Relevance
“…This suggests that the in vivo absorption mechanism of aprepitant from the nanocrystalline formulation is different than from the amorphous and DES formulations. A previous study of the absorption mechanism of aprepitant has suggested that the nanocrystals are able to reduce the resistance of the aqueous boundary layer next to the intestinal barrier ( Roos et al, 2017 ). Another study proposed that particle diffusion through the mucus layer increases the absorption of aprepitant ( Roos et al, 2018b ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the in vivo absorption mechanism of aprepitant from the nanocrystalline formulation is different than from the amorphous and DES formulations. A previous study of the absorption mechanism of aprepitant has suggested that the nanocrystals are able to reduce the resistance of the aqueous boundary layer next to the intestinal barrier ( Roos et al, 2017 ). Another study proposed that particle diffusion through the mucus layer increases the absorption of aprepitant ( Roos et al, 2018b ).…”
Section: Resultsmentioning
confidence: 99%
“…Several mechanistic pharmacokinetic studies have classified aprepitant as a biopharmaceutical classification system (BCS) class II drug, with solubility-limited oral drug absorption ( Wu et al, 2004 ; Litou et al, 2019 ; Shono et al, 2010 ). It has been suggested that the increased absorption of aprepitant from the nanocrystalline formulation is caused by increased diffusion of dissolved drug, colloid structures and nanoparticles in the aqueous boundary layer ( Roos et al, 2018a ; Roos et al, 2017 ; Roos et al, 2018b ).…”
Section: Introductionmentioning
confidence: 99%
“…The AAFE and AFE for each simulation are presented in Table 3. [37] In the present study, dissolution experiments in the Level II biorelevant media proved more useful than the equilibrium solubility experiments for identifying the relevant apparent solubility of the marketed aprepitant formulation. Thus, the experimental results demonstrated not only that the final concentration of aprepitant in the dissolution experiments was well above the equilibrium solubility, but also that application of the plateau values from the dissolution experiments led to a more accurate simulation of the plasma profiles.…”
Section: Pbpk Model and Simulationsmentioning
confidence: 94%
“…Jejunal and colonic lumen-to-blood effective permeability (P eff ) of the four model compounds was determined based on a modification of the method described by Sjögren et al, 2015 [18]. This method has been successfully implemented in human, dog and rat [4,[18][19][20][21]. In short, an input rate was acquired by deconvolution of the plasma concentration-time profiles following the intestinal perfusion using Phoenix software version 8.2 (Certara USA, Princeton, NJ, USA).…”
Section: Intestinal Effective Permeability (P Eff ) Calculationmentioning
confidence: 99%